Molecular characterization of the diatom, pseudo-nitzschia (bacillariophyceae) using the mitochondrial genetic marker, cytochrome oxidase I - Tan, Suh Nih (Universiti Malaysia Sarawak, UNIMAS, 2013)
Pseudo-nitzschia is a marine and planktonic chain-forming diatom. Some Pseudo-nitzschia species produce biotoxin, domoic acid (DA) which causes Amnesic Shellfish Poisoning (ASP) in humans and marine mammals. Species of Pseudo-nitzschia are difficult to distinguish under light microscope (LM). In this study, a total of 22 strains of Pseudo-nitzschia from Malaysian waters were identified based on morphological characteristics observed under LM and transmission electron microscope (TEM). A total of 17 stains were successfully identified; they are P. circumpora, P. cuspidata and P. pungens. A pair of genus-specific primer targeting the mitochondrial cytochrome oxidase I (COI) gene was developed in silico to infer the molecular phylogeny of Pseudo-nitzschia species. The primer specificity was tested using genomic DNA from clonal cultures. The designed primer was successfully amplified with a fragment length of 450 bp. A total of 12 strains of Pseudo-nitzschia species were successfully amplified. LSU rRNA gene of the cultures were also amplified to compare with the COI dataset. Genetic divergences of COI dataset and LSU rRNA dataset among the Pseudo-nitzschia taxa were ranged from 0 to 20.5 % and from 0 to 5 % respectively. Phylogenetic reconstruction revealed Pseudo-nitzschia taxa as a monophyletic group. However, the results showed incongruence in both COI and LSU phylogenies. As conclusion, the cultures and the species identity obtained in this study provide useful information on Pseudo-nitzschia study, and added to the database of harmful algal blooms research in the country.